Outcome of preemptive penile rehabilitation before bilateral cavernosal nerve injury in rats - ŞİMŞEK, FERRUH; TİNAY, İLKER (SPRINGER, 2010)
In this study, prophylactic penile rehabilitation (PR) with sildenafil before and after a cavernosal nerve (CN) injury was analyzed in an animal model. Thirty-six animals were divided into six groups as follows: (1) those with no CN injury (i.e., sham), (2) those with a bilateral CN injury (i.e., control), (3, 4) those with a bilateral CN injury treated with 10-20 mg/kg of sildenafil subcutaneously (SC) on a daily basis commencing 1 month prior to and after nerve injuries, respectively, (5, 6) those with a bilateral CN injury treated daily with 10-20 mg/kg of sildenafil SC after the nerve injuries, respectively. Mean arterial pressure (MAP) and intracavernosal pressure (ICP) were measured in response to CN stimulation to assess erectile function (EF). Neuronal nitric oxide synthase (nNOS) immunohistochemical analysis and real-time polymerase chain reaction (RT-PCR) were performed. The maximal ICP/MAP ratio was 60 +/- A 18% in the sham, 22 +/- A 5% in the control, 28 +/- A 9% in Group III, 45 +/- A 16% in Group IV, 45 +/- A 17% in Group V, and 49 +/- A 21% in Group VI. Although EF was improved with sildenafil treatment in a dose-dependent fashion, no statistically significant difference was observed between the preemptive and standard rehabilitation groups. Again, nNOS immunoreactivity and RT-PCR results showed the beneficial effect of sildenafil, but the study did not support the efficacy of preemptive rehabilitation when compared to the standard rehabilitation group. Although, a dose-response relationship was observed for PR treatment with sildenafil; i.e., outcomes improved at higher doses of sildenafil for PR, preemptive PR should not be pursued as an alternative rehabilitation modality.
Keywords: Cavernosal nerve; Penile rehabilitation; PDE-5 inhibitors; RADICAL PROSTATECTOMY; ERECTILE DYSFUNCTION; SEXUAL FUNCTION; SMOOTH-MUSCLE; PRESERVATION; RESECTION; MODEL